✔ 最佳答案
1)
1 - e^(-aπ)
───────
1 + e^(-aπ)
=
e^(aπ/2) - e^(-aπ/2)
───────────── ...... 由分子分母同乘 e^(aπ/2) 而得
e^(aπ/2) + e^(-aπ/2)
= ( 2sinh (aπ/2) ) / (2cosh (aπ/2))
= tanh (aπ/2)
2)
z² + 1
───────
z(z - e^(-ix))
=
(cosx + isinx)² + 1
──────────────────────────
(cosx + isinx)² - (cosx + isinx)(cosx - isinx)
=
(cosx + isinx)² + 1
───────────
(cosx + isinx)² - 1
=
cos(2x) + isin(2x) + 1
──────────────
cos(2x) + isin(2x) - 1
=
2cos²x + isin(2x)
───────────
isin(2x) - 2sin²x
=
2cos²x + i2sinx cosx
─────────────
i2sinx cosx - 2sin²x
=
cosx (cosx + isinx)
────────────
sinx (icosx - sinx)
=
cosx (cosx + isinx)
────────────
sinx i(cosx + isinx)
= cosx / (i sinx)